2016
DOI: 10.1002/2211-5463.12057
|View full text |Cite
|
Sign up to set email alerts
|

Activities of wild‐type and variant tissue‐type plasminogen activators retained on vascular endothelial cells

Abstract: We reported that tissue‐type plasminogen activator ( tPA ) secreted from vascular endothelial cells ( VEC s) is retained on the cell surface and effectively evokes both plasminogen activation and fibrin clot dissolution (fibrinolysis) on VEC s. Here, to evaluate possibly different behaviors of variants of tPA , we quantitatively assessed these two events separately using green fluorescent protein ( GFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, cardiovascular diseases, such as arterial stiffness, will develop when the function of endothelium is impaired. 22,23 Angiotensin II is reported to be one of the main factors that contribute to the process and development of arterial stiffness. The infiltration of inflammatory cells into the injured VECs could be induced by angiotensin II, which will be produced by inflammatory cells in turn.…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiovascular diseases, such as arterial stiffness, will develop when the function of endothelium is impaired. 22,23 Angiotensin II is reported to be one of the main factors that contribute to the process and development of arterial stiffness. The infiltration of inflammatory cells into the injured VECs could be induced by angiotensin II, which will be produced by inflammatory cells in turn.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses of the secretory dynamics of green fluorescent protein (GFP)-tagged tPA (tPA-GFP) from VECs using total internal reflection fluorescence (TIRF) microscopy revealed that tPA-GFP has unique secretory dynamics and is retained on the surface of VECs after its release from the granules [14]. This binding to VECs is dependent on the finger-domain and the kringle 2-domain of tPA, similar to its binding to fibrin [31], and also on a positively charged region consisting of K296, H297, R298, and R299 [32]. The secretion and the retention of tPA contribute to the effective activation of plg bound on the surface of VECs, and to effective fibrinolysis when fibrin is generated [15].…”
Section: Pasmentioning
confidence: 99%
“…The human EA.hy926 endothelial cell line [ 15 , 16 ] was obtained from the Cell Resource Center of Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences (Shanghai, China). S. cerevisiae BG was provided by the Institute of Modern Physics, Chinese Academy of Sciences (Lanzhou, China).…”
Section: Methodsmentioning
confidence: 99%